LIMIT THEOREMS FOR TOTAL NUMBER OF PARTICLES IN CRITICAL AGE-DEPENDENT BRANCHING PROCESSES - Lysetskyi, T. B.; Yeleiko, Ya. I. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2021)
In this paper we considercritical multitype age-dependent branching processes. It is known, that in case with constant transition probabilities in processes with immigration total numbers of particles in process born by t, divided by t2tends in probability to infinitely divisiblelaw, whose Laplace transform is explicitly given and in processes without immigration similar convergence holds but under the condition of non-extinction of process by t. Here we prove given results in case with variable transition probabilities.